S03-4 The sugar cane worker´s health and efficiency program in el salvador. (1st September 2016) - Bodin, Theo; Wegman, David H; Weiss, Ilana; Trabaninio, Ramón García; Glaser, Jason; Jarquín, Emmanuel; Hogstedt, Christer; Lucas, Rebekah; Wesseling, Catharina
Abstract : Introduction: CKD unrelated to diabetes or hypertension is epidemic in Central America. Sugarcane workers are among the most affected with heat stress and dehydration suggested as central factors. An intervention on these factors accompanied by productivity improvements was piloted in El Salvador during the 2014–15 harvest. Methods: The intervention adapted OSHA's Water.Rest.Shade (W.R.S.) hot work guidelines mid-way through the harvest for one inland cutting group. Water was provided in individual backpacks along with mobile shaded rest areas and scheduled rest periods. Ergonomically improved machetes and efficiency strategies were implemented for productivity. Health data (anthropometric, blood, urine, questionnaires) were collected four () times over six months. Daily wet bulb globe temperatures (WBGT) were recorded at inland and coastal worksites. The employer provided production records. Results: WBGT exceeded OSHA's limits for continuous work from 9 AM onwards and exceeded OSHA's highest limit (i.e., 30°C WBGT, requiring 45 min rest/hour) for 14% and 38% of hours worked at inland and coastal worksites, respectively. Post-intervention, self-reported water consumption increased 25%. Symptom surveys suggested reduction in most heat stress and/or dehydration symptoms. Daily production increased significantly post intervention exceeding productivity increases for most other cutting groups. Focus groups reported positive perception for both the W.R.S. program and the productivity improvements. Preliminary analysis of kidney function show decreased eGFR during the first two months of work before receiving the intervention but did not decrease further thereafter. Conclusion: A W.R.S. and efficiency intervention is feasible for manual sugarcane cutters. The intervention demonstrated reduced heat stress symptoms and higher intake of water. The combination of W.R.S. with efficiency measures also improved individual productivity without negative effects on health and well-being. Initial adoption by participants and the company is encouraging, as is interest from labour ministries of El Salvador and Costa Rica.